Search for a Hypothetical 16.7 MeV Gauge Boson and Dark Photons in the NA64 Experiment at CERN - Banerjee D.; Burtsev V. E. Vitaly Evgenjevich; Chumakov A. G. Aleksandr Grigorjevich; Crivelli P. Paolo; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Trifonov A. Yu. Andrey Yurievich; Vasilishin B. I. Bogdan Ivanovich (2018, 2018)
Title screen